ACADEMIC DISHONESTY ‘VERSUS’ PAKTA INTEGRITAS DAN PRESTISE SEKOLAH DALAM PELAKSANAAN UJIAN NASIONAL - Ahmad Zaini (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2014)
This article tries to elaborate the academic dishonesty vis a vis integrity pact and school prestise during the implementation of Ujian Nasional (National Examination). It has been known that National Examination is still debatable. Many disagree to do it because the final evaluation must be returned to the teachers. Whereas, government agrees to do so in order to standardize the result of teaching learning process. To guarantee fair play in the exam, all headmasters sign integrity pact. Therefore, students are motivated to study hard to pass the exam. Unfortunately, many students even their teachers and headmasters cheat in many ways to achieve high results. The background can be traced into many factors: internal and external of the students and the prestige of the schools which “must be maintained” by national and private schools.